Comparing the effect of office hysteroscopy with endometrial scratch versus office hysteroscopy on intrauterine insemination outcome: a randomized controlled trial. (November 2015) - El-Khayat, Waleed; Elsadek, Mostafa; Saber, Waleed
Abstract: Objective: To evaluate the role of endometrial injury in the cycle preceding ovarian stimulation for intrauterine insemination (IUI) cycle on the clinical pregnancy rate. Study design: This was a prospective randomized controlled trial which included three hundred and thirty two infertile women with an indication for IUI. The subjects were randomly divided into two groups. The intervention group (group A) ( n = 166) subjects underwent office hysteroscopy with endometrial injury using grasping forceps with teeth, while the control group (group B) ( n = 166) subjects underwent office hysteroscopy alone without endometrial injury. Primary outcome was clinical pregnancy rate. Results: There were no significant differences in baseline or clinical characteristics between the groups. There were no significant differences in clinical pregnancy rate [13.8% (23/166) versus 12% (20/166); RR 1.15 (95% CI 0.66–2.01), p = 0.62]. The abortion rate [4.3% (1/23) versus 15% (3/20); RR 0.29 (95% CI 0.03–2.57), p = 0.27], the multiple pregnancy rate [13% (3/23) versus 15% (3/20); RR 0.87 (95% CI 0.20–3.83), p = 0.85] and the live birth rate [13.6% (22/166) versus 10.4% (17/166); RR 1.28 (95% CI 0.71–2.32), p = 0.42]. Conclusion: There is no evidence of significant difference on the clinical pregnancy rate when endometrial scratching during hysteroscopy is compared to only hysteroscopy in women undergoing IUI.